A construct validation approach for exploring sustainability adoption in Pakistani construction projects - Ullah, Mehfooz; M., Waris; Hussain, Ammar; Rana, Faisal; Khan, Asadullah (MDPI, 2020)
Sustainable Project Management (SPM) is a novel theme in construction industries of developing countries and very little is known (so far) about the sustainability performance of construction projects in those settings. Accordingly, the quantitative measurement of SPM as a higher-order construct is not well established and lacks a holistic approach and homogenous taxonomy of indicators. This study explores the SPM practices of construction firms by validating SPM as a second-order construct in the Pakistani construction industry. Data were obtained from 146 construction firms, which were then analyzed using partial least square structure equation modeling. Results of the first and second level measurement model assessments showed that construction firms practice SPM, with varying degrees of attention paid to three sustainability aspects. Environmental dimension surfaced as the most important, in-terms of practice and social sustainability as least. The analysis of the second-order measurement model yielded significant results, thus, validating the higher-order structure of SPM. This study contributes to the field by presenting one of the first studies of its kind by focusing on the sustainability practices of construction firms by using a higher-order design of SPM construct within the context of developing countries